Immigrant labor and work-family decisions of native-born women - Delia Furtado (IZA World of Labor, 2015)
Many countries are reviewing immigration policy, focusing on wage and employment effects for workers whose jobs may be threatened by immigration. Less attention is given to effects on prices of goods and services. The effect on childcare prices is particularly relevant to policies for dealing with the gender pay gap and below-replacement fertility rates, both thought to be affected by the difficulty of combining work and family. New research suggests immigration lowers the cost of household services and high-skilled women respond by working more or having more children.
Keywords: D10; F22; J13; J22; R23; 330; immigration; female labor supply; fertility; childcare; time use